Некоторые типы синтагм с количественным значением в русском и литовском языках - Максимова, Г. В.; Labutis, Vitas (Baltistica, 1985)
Some types of syntagms with quantity meaning in Russian and LithuanianThe article examines the conditions under which the quantitative specification of the direct object (in particular the sense of ‘all’) takes place in the context of the perfective verb. The subject of this article is also syntagms of Russian and Lithuanian (verb of action + noun), which are the phenomena of morphological-lexical representation of the logical idea of multitude. The article shows the non-trivial semantic organization of the syntagms which is conditioned by the fact that the interpretation of this idea in the given languages is accompanied by the set of the other meanings. The main difference between Russian and Lithuanian syntagms consists in different ways by which elements of the semantic structure are reflected by elements of the surface structure, mainly by the verbal affixes.
Keywords: sintagma; kiekybė